The Correlation between Caries Status and Caries Risk Assesment with Body Mass Index in Children Living in Coastal Areas - Sutarto, Ayulistya Paramita; Paramita, Annisa Listya; Pinasti, Restika Anindya (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Indonesia is experiencing a double nutritional problem, undernutrition problem and overnutrition problem. Excess body weight has an effect on oral health. Underweight individuals have a risk of experiencing hyposalivation and caries. Changes the condition of the oral cavity that occur in the BMI category are related to the rate of saliva flow. BMI is positively correlated with salivary gland size.Method: The type of the research used analytical observational with a cross sectional approach. BMI is calculated by comparing body weight to height squared. The prevalence of caries is calculated using the decayed, missing, filled-teeth index (def-t or DMF-T). Caries risk assessment is carried out using the CAMBRA method.Result: 22.8% of children with underweight BMI had a caries index of 4.34 and 50% had a high risk of caries. The results of the Spearman correlation test between BMI and the caries index obtained a significance value of 0.046, so it can be concluded that there is a relationship between BMI and the caries index. The results of the correlation test between BMI and caries risk assessment obtained a significance value of 0.070, so it can be concluded that there is no relationship between BMI and caries risk.Conclusion: There is a significant relationship between Body Mass Index and the caries index. There is no significant relationship between Body Mass Index and caries risk assessment using the CAMBRA method in children living in coastal areas